2013
DOI: 10.1112/plms/pds097
|View full text |Cite
|
Sign up to set email alerts
|

Generation of finite quasisimple groups with an application to groups acting on Beauville surfaces

Abstract: We develop theorems which produce a multitude of hyperbolic triples for the finite classical groups. We apply these theorems to prove that every quasisimple group except Alt (5) and SL 2(5) is a Beauville group. In particular, we settle a conjecture of Bauer, Catanese and Grunewald which asserts that all non‐abelian finite quasisimple groups except for the alternating group Alt (5) are Beauville groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(88 citation statements)
references
References 51 publications
(213 reference statements)
0
87
0
1
Order By: Relevance
“…According to a recent preprint by Fairbairn, Magaard and Parker [10], this conjecture is true. Similarly, Theorem 5.1 raises the question of which other quasisimple groups admit strongly real Beauville structures.…”
Section: Casementioning
confidence: 51%
See 1 more Smart Citation
“…According to a recent preprint by Fairbairn, Magaard and Parker [10], this conjecture is true. Similarly, Theorem 5.1 raises the question of which other quasisimple groups admit strongly real Beauville structures.…”
Section: Casementioning
confidence: 51%
“…Garion, Larsen and Lubotzky [12] have shown that all but finitely many non-abelian finite simple groups are Beauville groups. Subsequently Guralnick and Malle [15] have extended this to all such groups except A 5 , thus proving the conjecture of Bauer, Catanese and Grunewald, while Fairbairn, Magaard and Parker [10] have extended this further to all finite quasisimple groups except A 5 ∼ = L 2 (5) and its central cover SL 2 (5).…”
Section: Introductionmentioning
confidence: 95%
“…This is for the positive side. On the negative side we essentially prove a conjecture of Marion proposed in [21]: in that paper he studied (a, b, c)-generation of finite quasisimple (2,4,6), (2,6,6), (2, 6, 10) (3,4,4), (3,6,6), (4,6,12) 5,7,8,9,10,11,13,15,16,17,19,22,23,25,29,31, 37, 43} (r ≥ 4) (2,3,8) r ∈ {4, 5, 7, 9, 10, 11, 13, 17, 19, 25} (2,3,9) r ∈ {4, 5, 7, 10, 11, 13, 19} (2,3,10) r ∈ {4, 5, 7, 11, 13} (2,3,11) r ∈ {4, 5, 7, 13} (2,3,12) r ∈ {4, 5, 7, 13} (2, 3, c), c ≥ 13 r ∈ {4, 5, 7} (2,4,…”
Section: Introductionmentioning
confidence: 61%
“…Turning to general hyperbolic triples of integers, any finite simple group, being 2-generated, is a quotient of some triangle group T and in fact can be so realized in many independent ways. See for example [10,9,12] and the references therein establishing that every finite simple group other than Alt 5 admits an (unmixed) Beauville structure.…”
Section: Introductionmentioning
confidence: 99%
“…Shortly after publication of our article, it was brought to our attention that the first six results related to the generation of classical groups by two primitive prime divisor elements in [1, Section 3] can already be found in the much earlier 1998 work of Niemeyer and Praeger [2]. The connections are as follows: [2] should be cited in place of [1] for all of these statements.…”
mentioning
confidence: 97%